Effects of agricultural waste-based conditioner on ultrasonic-aided activated sludge dewatering. Issue 54 (13th June 2015) - Guo, Shaodong; Qu, Fangshu; Ding, An; He, Junguo; Yu, Huarong; Bai, Langming; Li, Guibai; Liang, Heng
<x xml:space="preserve">Abstract</x> The effects of agricultural wastes on ultrasonic-aided activated sludge dewaterability were investigated in this study.